Cryopreservation of PLBs of Brassidium Fly Away Using Encapsulation-Dehydration Techniqu - Rajasegar, Arulvilee; Poobathy, Ranjetta; Rathinam, Xavier; Oyunbileg, Yungeree; Subramaniam, Sreeramanan (National University of Mongolia, 2015)
In vitro grown protocorm-like bodies (PLBs) of Brassidium Fly Away orchid hybrid were cryopreserved using encapsulation- dehydration technique. The viability of the cryopreserved cells was determined by 2,3,5-triphenyltetrazolium chloride (TTC) assay. For the preculture treatment, the PLBs were excised into two standard sizes of 1-2 and 4-5 mm and were precultured on half-strength Murashige and Skoog (MS) semi solid medium supplemented with diff erent concentrations of sucrose (0, 0.2, 0.4, 0.6, 0.8 and 1.0M). The PLBs size 4-5 mm and 0.6 M sucrose concentration was selected based on highest viability obtained in TTC assay. The PLBs were encapsulated for 30 minutes using 3% (w/v) liquid sodium alginate medium supplemented with 0.4M sucrose and 0.1M calcium chloride and osmoprotected in 0.75M sucrose solution for 24 hours at 25°C. The beads were then dehydrated using 50g heat-sterilised silica gel for four hours, cryopreserved for 24 hours, thawed in a 40±2°C water bath for 90 seconds, and regenerated in semi-solid half-strength. Biochemical analyses were conducted and the cryopreserved PLBs had produced lower content of chlorophyll while the highest specifi c peroxidase activity was observed in cryopreserved PLBs.